THE EFFECT OF PROMOTION STRATEGY ON BUYER DECISIONS AT THE SINAR MAS JAYA STORE IN GUNUNGSITOLI CITY - Selvius Vincentius Waruwu; Otanius Laia; Idarni Harefa; Yupiter Mendrofa (LPPM YPITI, 2026)
This study aims to determine the effect of promotional strategies on purchasing decisions at the Sinar Mas Jaya store in Gunungsitoli City. The main objective of this study is to determine how much influence promotional strategies have on purchasing decisions at the Sinar Mas Jaya store in Gunungsitoli City. The type of research used in this study is quantitative research, the number of samples in this study was 82 people. Based on the coefficient of determination test, the R Square value of 0.61 or 61% indicates that the Promotion Strategy variable has a positive effect on the Purchase Decision variable Y by 61%. Based on the test results, t-count of 2.283> t-table of 1.664 and at a significant level of 0.025 <0.05. So it can be concluded that Ho is rejected Ha is accepted. In other words, the Promotion strategy has a significant influence on Purchasing decisions at the Sinar Mas Jaya Store in Gunungsitoli City.